Prenatal mold exposure is associated with development of atopic dermatitis in infants through allergic inflammation - Eun Lee; Kil Yong Choi; Mi-Jin Kang; So-Yeon Lee; Jisun Yoon; Hyun-Ju Cho; Sungsu Jung; Si Hyeon Lee; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; et al. (Jornal de Pediatria, 2020)
Objective: Mold exposure in early life may be associated with development of atopic dermatitis; however, studies of this link are inconclusive and evidence for the underlying mechanism(s) is lacking. This study identified the association between the time of mold exposure and development of atopic dermatitis and investigated the underlying mechanisms. Method: The association between atopic dermatitis and mold exposure was examined in the Cohort for Childhood Origin of Asthma and Allergic Diseases birth cohort study (n = 1446). Atopic dermatitis was diagnosed at 1 year of age by pediatric allergists. Exposure to mold was assessed by questionnaire. The Illumina MiSeq platform was used to examine the environmental mycobiome in 20 randomly selected healthy infants and 20 infants with atopic dermatitis at 36 weeks of gestation. Results: Prenatal, but not postnatal, mold exposure was significantly associated with atopic dermatitis (adjusted odds ratio, 1.36; 95% confidence interval, 1.01–1.83). Levels of total serum IgE at 1 year of age were higher in infants with atopic dermatitis exposed to mold during pregnancy than in healthy infants not exposed to mold during pregnancy (p = 0.021). The relative abundance of uncultured Ascomycota was higher in infants with atopic dermatitis than in healthy infants. The relative abundance of uncultured Ascomycota correlated with total serum IgE levels at 1 year of age (r = 0.613, p < 0.001). Conclusion: Indoor mold exposure during the fetal period is associated with development of atopic dermatitis via IgE-mediated allergic inflammation. Avoidance of mold exposure during this critical period might prevent the development of atopic dermatitis. Resumo: Objetivo: A exposição ao mofo no início da vida pode estar associada ao desenvolvimento de dermatite atópica; contudo, os estudos sobre esse vínculo são inconclusivos e faltam evidências dos mecanismos subjacentes. Identificamos a associação entre o momento da exposição ao mofo e o desenvolvimento de dermatite atópica e investigamos os mecanismos subjacentes. Método: A associação entre dermatite atópica e exposição a mofo foi examinada em um estudo de coorte de nascimento da Origem da Asma e de Doenças Alérgicas em Crianças (COCOA) (n = 1446). A dermatite atópica foi diagnosticada em pacientes com um ano de vida por pediatras alergistas. A exposição ao mofo foi avaliada por um questionário. A plataforma Illumina MiSeq foi utilizada para examinar o microbioma ambiental em 20 neonatos saudáveis escolhidos aleatoriamente e 20 com dermatite atópica a 36 semanas de gestação. Resultados: A exposição pré-natal, porém não pós-natal, ao mofo foi significativamente associada à dermatite atópica (razão de chances ajustada, 1,36; intervalo de confiança de 95%, 1,01-1,83). Os níveis séricos totais de Imunoglobulina E (IgE) no primeiro ano de vida foram maiores em neonatos com dermatite atópica expostos a mofo durante a gravidez do que em neonatos não expostos a mofo durante a gravidez (p = 0,021). A abundância relativa de Ascomycota não cultivado foi maior em neonatos com dermatite atópica do que em neonatos saudáveis. A abundância relativa de Ascomycota não cultivado correlacionou-se com os níveis séricos totais de IgE no primeiro ano de vida (r = 0,613, p < 0,001). Conclusão: A exposição ao mofo no ambiente domiciliar durante a gravidez está associada ao desenvolvimento de dermatite atópica por meio de reação alérgica mediada por IgE. A prevenção à exposição ao mofo durante o período crítico da gravidez pode prevenir o desenvolvimento de dermatite atópica. Keywords: Allergic inflammation, Atopic dermatitis, Environment, Mold, Mycobiome, Prenatal, Palavras-chave: Reação alérgica, Dermatite atópica, Ambiente, Mofo, Microbioma, Pré-natal